THEORIES OF DEVELOPMENT POLES APPLICABILITY IN THE EUROPEAN UNION NEIGHBOURHOOD CROSS-BORDER FRAME - Marcela SLUSARCIUC (Studia Universitatis Babeş-Bolyai Negotia, 2015)
Nowadays the cross-border cooperation is promoted through policies and with financial help involved in order to increase the territorial cohesion along the national borders of EU and to increase the relationships with the neighbour countries. At a certain degree the areas along the borders can be considered regions that, being peripheric, need development despite the specificity brought by the different statuses. The paper has as central the concept that was first put forth systematically by Francois Perroux, being now into use in many countries, both in theoretical discussions and public policy programs. The promotion of regional development centres will serve as focal point and incentive for further development. Such a regional concentration helps through the benefits of technological external economies and makes the growth centre attractive to entrepreneurs, thus initiating further development. We examine the actual approaches in the literature on the economic growth, development poles and their main characteristics based on which we are able to identify the applicability of these theories in a cross-border frame in our future researches.